Targeted gene addition to a predetermined site in the human genome using a ZFN-based nicking enzyme - Wang, Jianbin; Friedman, Geoffrey; Doyon, Yannick; Wang, Nathaniel S.; Li, Carrie Jiaxin; Miller, Jeffrey C.; Hua, Kevin L.; Yan, Jenny Jiacheng; Babiarz, Joshua E.; Gregory, Philip D.; Holmes, Michael C. (Genome Research, 2012)
Zinc-finger nucleases (ZFNs) drive highly efficient genome editing by generating a site-specific DNA double-strand break (DSB) at a predetermined site in the genome. Subsequent repair of this break via the nonhomologous end-joining (NHEJ) or homology-directed repair (HDR) pathways results in targeted gene disruption or gene addition, respectively. Here, we report that ZFNs can be engineered to induce a site-specific DNA single-strand break (SSB) or nick. Using the CCR5-specific ZFNs as a model system, we show that introduction of a nick at this target site stimulates gene addition using a homologous donor template but fails to induce significant levels of the small insertions and deletions (indels) characteristic of repair via NHEJ. Gene addition by these CCR5-targeted zinc finger nickases (ZFNickases) occurs in both transformed and primary human cells at efficiencies of up to ∼1%–8%. Interestingly, ZFNickases targeting the AAVS1 “safe harbor” locus revealed similar in vitro nicking activity, a marked reduction of indels characteristic of NHEJ, but stimulated far lower levels of gene addition—suggesting that other, yet to be identified mediators of nick-induced gene targeting exist. Introduction of site-specific nicks at distinct endogenous loci provide an important tool for the study of DNA repair. Moreover, the potential for a SSB to direct repair pathway choice (i.e., HDR but not NHEJ) may prove advantageous for certain therapeutic applications such as the targeted correction of human disease-causing mutations.
10.1101/gr.122879.111